Nutritional composition of 10 selected traditional wheat-based malaysian methin east coast of Malaysia: an updates of Malaysian food composition database - Magini, Shazwani (Universiti Sains Malaysia, 2013)
This study is part of national project to update Malaysian Food Composition Database focuses on the data from Eastern region of the Peninsular Malaysia. The justification of the present study was to provide the knowledge on food composition data from selected traditional wheat-based Malaysian kuih. The objective of the present study was to determine the proximate composition of 10 selected traditional wheat-based Malaysian kuih in East Coast of Malaysia. A total number of 10 selected traditional wheat-based Malaysian kuih were sampled from the local restaurants and stalls within Kota Bharu city, Kelantan. The types of kuih chosen in the study were Apam Seri Ayu, Bahulu Kemboja, Kek Pisang, Cucur Bawang, Karipap Sardin, Cara Berlauk, Cara Manis, Pau Goreng/Sambal, Lepat Labu and Roti Jala. The nutrients analyzed include energy, moisture, protein, fat, carbohydrate and ash. The sampling plans used were following standard methods from the protocol for sampling and method of analysis for Malaysian Food Composition Database (FCD). The results of the study were tabulated and expressed as per 100 g edible portion. The ranges of energy in traditional wheat-based Malaysian kuih were 147 kcal to 464 kcal. Meanwhile, the range mean values of water content were 21.7 g to 63.0 g. For protein and fat content, the range mean values were 6.3 g to 17.6 and 1.2 g to 32.1 g, respectively. In addition, the range mean values of carbohydrate and ash were 9.7 g to 46.6 g and 0.9 g to 2.5 g, respectively. In summary, Cara Berlauk are good choice of kuih that providing the lowest level in energy, carbohydrate and fat while having the highest level in moisture, protein and also comparable value of ash content. Thus, it could be recommended to be consumed by those who are concern about their dietary intake.